The effects of 1-131 on different types of cancer Cell lines - Yusoff, Nik Nur Nadiah Nik (Universiti Sains Malaysia, 2015)
The aim of this study is to investigate the effect of 1-131 on different type of cancer cell lines. HeLa, T24, and DBTRG-05 cells exposed to radioiodine-131 of activity 100, 200, 300, 400, and 500 pCi were incubated at 37°C temperature in 1 hour, 2 hours and 3 hours. The cells then washed with PBS and being trypsinized followed by performing measurement using well counter to acquire the cell counts. Percentage uptake was calculated, proceeded with the cells viability and clonogenic assay procedure. HeLa cells uptake was found to be inversely correlated to the radioactivity and uptake by DBTRG-05 cells was significantly high than compare to HeLa and T24 cells. T24 cells uptake was increased with activity in 3 hours incubation time. As for the cells viability, result obtained was increased by time in HeLa that reverse to T24 and DBTRG-05 cells which viability was reduced by time but the viability with respect to activity was not significantly obtained. Meanwhile, the use of high activity 1-131 within few days was found suppressed the proliferation of cancer cells especially for DBTRG-05 cells followed by T24 and HeLa.. The findings of this study suggest that the cellular uptake of 1-131, cells viability and proliferation were highly dependent on cells metabolism, mitotic rate, occurrence of apoptosis, doubling time, cells radiosensitivity, and so on with consideration of some limitations.